Pengaruh Model Pembelajaran Think Pair Share Terhadap Kemampuan Komunikasi, Pemecahan Masalah Dan Hasil Belajar IPA Siswa Kelas V - Fadhilah Hukmiah; Rosleny Babo; Idawati (Program Studi Manajemen Pendidikan, 2023)
The purpose of this study was to determine the effect of the application of the Think Pair Share learning model on communication skills, problem solving abilities and learning outcomes of students of class V MIN 4 Selayar Islands. This type of research is a pretest-posttest control group design. The number of samples in this study were 30 people, consisting of 15 people in the experimental class and 15 people in the control class. The data collection method used is the learning achievement test to measure learning outcomes, observation to measure communication and problem solving abilities, and documentation. The data analysis technique used is descriptive statistical approach, imperential analysis and hypothesis testing. The research results obtained were 1) students' communication skills were 0.009 <0.05, which means H1 was accepted and H0 was rejected, that is, there was an effect of the application of the Think pair share learning model on students' communication skills. 2) students' problem-solving ability is 0.021 <0.05, which means that H1 is accepted and H0 is rejected, that is, there is an effect of applying the Think Pair Share learning model to students' problem-solving abilities. 3) student learning outcomes are 0.001 <0.05, which means H1 is accepted and H0 is rejected, that is, there is an influence of the application of the Think pair share learning model on social studies learning outcomes for students of MIN 4 Selayar Islands.